Helicobacter pylori in tonsillar and adenoid tissue and its possible role in oropharyngeal carcinogenesis - Lukes, P; Astl, J; Pavlík, E; Potuzníková, B; Sterzl, I; Betka, J (Folia biologica, 2008)
Helicobacter pylori is a well-known gastric pathogen. It plays a major role in the pathogenesis of chronic gastritis, duodenal and gastric ulcers, adenocarcinoma and gastric lymphoma. HP infection is one of the most common bacterial infections worldwide. Recently, the oral cavity was proposed as an extragastric reservoir of HP infection. HP was detected by culture and PCR in both dental plaque and saliva. It is supposed that HP infection can cause the same immunological changes in the oropharyngeal mucosa as in gastric mucosa and can also contribute to the progression of oropharyngeal diseases. HP can induce production of different cytokines and regulatory molecules, which are suggested to play a role in carcinogenesis of the oropharynx. Only a few studies have explored the presence of HP in tonsillar and adenoid tissue, where MALT is present similar to the gastric mucosa. The results of these studies were inconsistent. The question of persistence of HP in tonsillar and adenoid tissue and its role in the pathogenesis of oropharyngeal diseases still remains unclear. In this review, recent findings about oral HP are considered. Possibilities of diagnostics of HP in oral specimens are discussed.
Keywords: Palatine Tonsil; adenoidy; cytokiny; nádory orofaryngu; krční mandle; Adenoids; Humans; Helicobacter Infections; Oropharyngeal Neoplasms; Helicobacter pylori; žaludeční sliznice; lidé; Gastric Mucosa; Oropharynx; infekce vyvolané Helicobacter pylori; orofarynx; Cytokines